Prevention of insulin resistance with Hibiscus sabdariffa Linn. extract in high-fructose fed rat (Faculty of Medicine Universitas Indonesia, 2014)
Background: Dyslipidemia and stress oxidative play an important role as the cause of insulin resistance. One herb that has potent antioxidant effect and may improve dyslipidemia is Hibiscus sabdariffa Linn. The aim of this study was to evaluate the effect of Hibiscus sabdariffa Linn. extract on fasting blood glucose level, fasting blood insulin level, and insulin resistance index (HOMA-IR) in high-fructose fed rat. Methods: This was an experimental study in 25 Sprague-Dawley rats which were administered with a high-fructose diet (10% ad libitum) and Hibiscus sabdariffa Linn. extract at a dose of 100, 200, and 400 mg/kgBW/d simultaneously for 5 weeks. At the end of study, fasting blood glucose level, fasting blood insulin level and insulin resistance index (HOMA-IR) were measured. Results: Fasting blood glucose, blood insulin, and HOMA-IR level of rats given high-fructose diet with Hibiscus sabdariffa Linn. at dose 100 mg/kgBW/d were not significantly different than the group of rats given only high-fructose fed. While at the dose of 400 mg/kgBW/d, they were significantly lower than the group given only high-fructose fed (4.84 mmol/L vs 6.11 mmol/L, 0.07 µU/L vs 0.3 µU/L, and 0.02 vs 0.08 respectively). Conclusion: Oral administration of Hibiscus sabdariffa Linn. could prevent the development of insulin resistance induced by high-fructose diet in the rat.